If/then [compact disc] : a new musical : original Broadway cast recording - Kitt, Tom (Masterworks Broadway, 2014)
Fresh off performing the Oscar-winning hit song Let It Go from Frozen, Idina Menzel returns to Broadway for the first time since her Tony Award-winning role in Wicked. She is joined in the cast by former Rent star Anthony Rapp.